2006
DOI: 10.1111/j.1365-2222.2006.02547.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between neurokinin 2 receptor gene polymorphisms and serum vascular endothelial growth factor levels in patients with toluene diisocyanate‐induced asthma

Abstract: SummaryBackground Among the various pathogenic mechanisms of toluene diisocyanate (TDI)-induced asthma, a contribution from neurogenic inflammation has been suggested. Objective To evaluate neurokinin 2 receptor (NK2R) gene polymorphisms in association with the clinical phenotype of TDI-induced asthma, 70 TDI-induced occupational asthma (TDI-OA)patients, 59 asymptomatic exposed controls (AEC), and 93 unexposed healthy controls (NC) were enrolled in the study. Methods Two single-nucleotide polymorphisms (SNPs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…63 A role for neurogenic inflammation in isocyanate asthma has been suggested by a Korean study. 64 The authors investigated whether neurokinin 2 receptor (NK2R) gene polymorphisms are associated with the clinical phenotype of TDI asthma. No significant differences in allele, genotype, or haplotype frequencies of the NK2R polymorphisms were present among the groups of subjects with asthma, asymptomatic exposed subjects, and healthy controls.…”
Section: Genetic Aspectsmentioning
confidence: 99%
“…63 A role for neurogenic inflammation in isocyanate asthma has been suggested by a Korean study. 64 The authors investigated whether neurokinin 2 receptor (NK2R) gene polymorphisms are associated with the clinical phenotype of TDI asthma. No significant differences in allele, genotype, or haplotype frequencies of the NK2R polymorphisms were present among the groups of subjects with asthma, asymptomatic exposed subjects, and healthy controls.…”
Section: Genetic Aspectsmentioning
confidence: 99%
“…No significant difference in allele, genotype, or haplotype frequencies of these two SNPs was seen, but subjects with the NK2R 7853GG genotype had higher serum vascular endothelial growth factor (VEGF) levels than those with GA or AA among the TDI-exposed workers, suggesting that the NK2R 7853GG genotype contributes to increased serum VEGF levels, resulting in airway inflammation after TDI exposure, which may be mediated by neurogenic ROS 26. These results suggest that the NK2R 7853G>A polymorphism is a candidate biomarker for TDI OA.…”
Section: Genetic Markersmentioning
confidence: 99%
“…6 In addition, a genome-wide association study of TDI-exposed workers revealed that alpha T-catenin single-nucleotide polymorphisms (SNPs) were significantly associated with the phenotype of TDI-induced OA. Moreover, two SNPs of TRPM8 (rs10803666 and rs12434022, which have been mapped to the TRPM8 gene and are located on 2q37 and 14q31) showed significant associations using a recessive analysis model.…”
Section: Introductionmentioning
confidence: 99%